Difference of Schirmer Test Results Before and After Using Smartphones with Various Screen Brightness Levels - Dodik Dumadi; Maharani Maharani; Tanti Ajoe Kesoema; Riski Prihatningtias (Diponegoro International Medical Journal, 2021)
Background : The use of smartphones and other digital devices such as laptops and tablets is familiar in Indonesian society. Excessive uses of the devices are associated with dry eye syndrome and tear film dysfunction. The intensity of blue light when penetrating the eye is believed to affect tear film stability. Thus it will encourage tear evaporation which proved by Schirmer test.Objective : To find out the difference of Schirmer test results before and after using a smartphone with  various screen brightness levels.Methods : This study used pretest-posttest quasi-experimental study. The research subjects were students of the Faculty of Medicine, Diponegoro University (n = 30) who were selected by purposive sampling. In this study, the research subjects used smartphones for an hour with a predetermined screen brightness level, with the same room lighting. Before and after treatment the subject was measured the quantity of tears using the Schirmer test. Data were analyzed using the Wilcoxon test, Mann Whitney U test, and Kruskal Wallis test.Results : The average pretest result on low brightness was 25,60 ± 9,44 and the post-test result was 17,60 ± 8,45. The pre-test result on medium brightness was 27,90 ± 9,46 and the post-test result was 24,80 ± 10,46. The pre-test result on high brightness was 23,60 ± 6,80 and the post-test result was 19,10 ± 7,95. The Schirmer test results before and after using smartphones with low brightness showed a significant different (P<0.05) and there was no significant difference for the pre-post test using smartphones with medium and high brightness. Comparison of Schirmer test results on low, medium and high screen brightness did not show a significant difference.Conclusion : There is no significant difference between the Schirmer test results among low, medium and high screen brightness after one hour of smartphone usage.